Respuesta :

Answer:

The correct answer is option C.

Step-by-step explanation:

To find a substitute for the variable y in the second equation, you need to first find out what y is equivalent to in the first equation: in other words, isolate the variable. [tex]2y-x=6[/tex] ⇒ [tex]2y = x + 6[/tex] ⇒ [tex]y = 0.5x + 3[/tex]. Since y is equivalent to [tex]0.5x+3[/tex] in the first equation, that means you can use that to replace y in the second equation, so the correct choice is C.

I would say c for the right answer